2013
DOI: 10.1063/1.4817954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a floating electrode on a plasma jet

Abstract: Two kinds of floating electrode, floating dielectric barrier covered electrode (FDBCE) and floating pin electrode (FPE), which can enhance the performance of plasma jet are reported. The intense discharge between the floating electrode and power electrode decreased the voltage to trigger the plasma jet substantially. The transition of plasma bullet from ring shape to disk shape in the high helium concentration region happened when the floating electrode was totally inside the powered ring electrode. The enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…When the helium gas flow reaches the ground electrode, it flows radially along the surface of the electrode, which is similar to the simulation results presented in Ref. [21].…”
Section: Discharge Characteristics Of a Dpe Plasma Jetsupporting
confidence: 88%
“…When the helium gas flow reaches the ground electrode, it flows radially along the surface of the electrode, which is similar to the simulation results presented in Ref. [21].…”
Section: Discharge Characteristics Of a Dpe Plasma Jetsupporting
confidence: 88%
“…The appearance of the return stroke in ionization waves is known from streamer discharges [69] as well as the formation of glow discharges [70]. They were observed experimentally in plasma jets as well when the discharge was interacting with a metallic target [14,15,17] and with water [71]. Simulations have demonstrated that the appearance of the return stroke is highly dependent on the electrical properties of the target [10,16,18].…”
Section: Return Stroke or Surface Ionization Wavesmentioning
confidence: 98%
“…Changes in the biological targets’ capacitance change the surface charges deposited by the plasma onto the biological target . The reason for this is that higher relative permittivity increases capacitance that results in more charging at the surface leading to an increase in surface charge deposition. Surface charge deposition is increased because higher relative permittivity promotes a faster more intense ionization wave that creates a highly conductive channel between the electrode and the biological target. , Vice versa is true for biological targets with lower relative permittivity. Different permittivity values of biological targets commonly treated by plasma are given in Table . ,, Permittivity of the biological target can also change depending on its physical and chemical condition.…”
Section: Parameters To Monitor At the Plasma–biological Target Interfacementioning
confidence: 99%